Analisis Risiko the Lowest Bid Method dalam Public Procurement di Kementerian Keuangan - Arifin, Zanuar; Arviansyah, Arviansyah (Penerbit Goodwood, 2024)
Purpose: This study provides a detailed analysis of the advantages and disadvantages of using the lowest bid price method in public tenders. Research methodology: This study uses a quantitative method. This study uses a questionnaire survey, then the data from the questionnaire is analyzed using the Relative Importance Index (RII). This study also analyzes descriptive statistics on construction procurement data. Results: The findings indicate that the lowest bid method has several benefits, including increasing competition and transparency in the selection process. However, there are also some shortcomings that management should understand. Limitations: The study is limited by its focus on cases within the Ministry of Finance in Indonesia and the use of self-reported data from questionnaires, which may differ from practices in other contexts. The data used in this study comes from a certain period of time, so it can’t explain all procurement performance. Contribution: The research contributes to the fields of public construction procurement.